Association of amount and duration of NRT use in smokers with cigarette consumption and motivation to stop smoking: A national survey of smokers in England. (January 2015) - Beard, Emma; Bruguera, Carla; McNeill, Ann; Brown, Jamie; West, Robert
Abstract: Introduction: Clinical trials have found that the use of nicotine replacement therapy (NRT) to reduce cigarette consumption results in significant declines in cigarette consumption and increases smokers' propensity to quit. However, observational "real-world" studies have found much smaller effects. This may be because of low levels of NRT use. This study examined the association between amount and duration of NRT use amongst those attempting to reduce their cigarette consumption with motivation to quit and cigarette consumption. Methods: Data came from 2, 158 smokers who took part in the Smoking Toolkit Study. A representative survey of smokers in England aged 16 +. Results: Only 54.4% of patch users and 32.2% of non-transdermal NRT users reported using NRT with a frequency that would be expected to substantially influence cigarette consumption (4 + units per day for acute NRT forms and at least daily for transdermal patches). Those using the patch at or above this threshold smoked 1.3 cigarettes per day fewer than those using it below the threshold ( p = 0.059), whilst those using non-transdermal NRT at or above this threshold smoked 0.9 cigarettes less per day ( p = 0.022). In both cases, those using NRT more frequently had greater motivation to quit. Less than 1/5th of participants reported using a combination of NRT products. Use of NRT long-term was associated with lower motivation to quit and higher cigarette consumption. Conclusion: Smokers attempting to reduce their cigarette intake are underusing NRT and this is associated with cigarette consumption and motivation to quit. These findings may explain why population-based studies have failed to report similar findings to clinical trials. Highlights: Clinical trials demonstrate that NRT for smoking reduction is efficacious. At the population level, NRT increases motivation to quit but does not reduce intake. It may be that smokers are not using enough NRT or for long enough. The current study assessed the extent of dual NRT and cigarette use. Findings suggest that effectiveness may partially depend on extent of use.